Fair Use Quotation Licenses: A Private Sector Solution To DMCA Takedown Abuse on YouTube - Chung, Timothy S. (The Columbia Journal of Law & the Arts, 2020)
Part I of this Note covers the history of the fair use doctrine and its interplay with the DMCA, specifically within the context of video-hosting platforms like YouTube, and examines how recent case law developments concerning the DMCA have fostered an environment that is ripe for abuse. Part II then argues that most content creators on YouTube have little to no recourse if their fair use creations are flagged as infringing content by right holders who request DMCA takedowns. Specifically, YouTube’s copyright policies and the excessive costs of litigation disincentivize users from fighting DMCA takedowns or pursuing legal actions to counteract bad faith behavior. As a consequence, the fair use defense is inaccessible to most YouTube content creators. Finally, Part III proposes the implementation of a quotation licensing scheme as one option to mitigate DMCA takedown abuse on YouTube. In recognizing the value of fair use for incentivizing creation, this scheme would contractually carve out a small exception to infringement, permitting limited appropriation of fellow users’ content on YouTube.